Clinical efficacy of antivirals against novel coronavirus (COVID-19): A review - Shahamah Jomah; Syed Mohammed Basheeruddin Asdaq; Mohammed Jaber Al-Yamani (Elsevier, 2020)
The unprecedented challenge faced by mankind due to emergence of coronavirus 2019 (COVID-19) pandemic has obligated researchers across the globe to develop effective medicine for prevention and treatment of this deadly infection. The aim of this review is to compile recently published research articles on anti-COVID 19 management with their benefits and risk to facilitate decision making of the practitioners and policy makers. Unfortunately, clinical outcomes reported for antivirals are not consistent. Initial favorable reports on lopinavir/ritonavir contradicted by recent studies. Ostalmovir has conflicting reports. Short term therapy of remdesivir claimed to be beneficial. Favipiravir demonstrated good recovery in some of the cases of COVID-19. Umifenovir (Arbidol) was associated with reduction in mortality in few studies. Overall, until now, U.S. Food and Drug administration issued only emergency use authorization to remdesivir for the treatment of suspected or laboratory-confirmed COVID-19 in adults and children hospitalized with severe disease.